2023
DOI: 10.1136/bmjsem-2023-001722
|View full text |Cite
|
Sign up to set email alerts
|

Quest for clarity: investigating concussion-related responsibilities across the New Zealand Rugby Community System

Danielle M Salmon,
Jason Chua,
James C Brown
et al.

Abstract: There is a growing concern around concussions in rugby union, at all levels of the game. These concerns highlight the need to better manage and care for players. However, consistency around concussion-related responsibilities of stakeholders across the community rugby system remains challenging. Taking a systems thinking approach, this pragmatic, qualitative descriptive study explored key stakeholder groups within New Zealand’s community rugby system’s perceptions of their own and others’ concussion-related re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Rather, downloading the final decision to the match official has provided the opportunity for others (e.g., athletes and coaches) to avoid responsibility. Salmon et al ( 55 ) have similarly identified responsibility concerns in coordinating concussion management. Match officials accepted their role in ensuring the safety of participants, aligning with Clacy et al ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rather, downloading the final decision to the match official has provided the opportunity for others (e.g., athletes and coaches) to avoid responsibility. Salmon et al ( 55 ) have similarly identified responsibility concerns in coordinating concussion management. Match officials accepted their role in ensuring the safety of participants, aligning with Clacy et al ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…In reality, physiotherapists are often involved and confident to identify and manage individuals with suspected concussions while waiting for a medical doctor appointment (Frémont et al, 2022;Maxtone et al, 2020;McGrann & Keating, 2012;Salmon, Chua, et al, 2023). To initiate care under the current ACC restrictions, physiotherapists use other read codes that are within their scope, such as neck sprains or head contusions (Kennedy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%